Laparoscopic Distal Pancreatectomy of a Solid Pseudopapillary Tumor (SPT) Achieves Long-Term Oncologic Safety and Multiorgan Preservation - ElHaddad, Ahmed; Gasparella, Paolo; Castellani, Christoph; Singer, Georg; Sorantin, Erich; Zach, Klara; Till, Holger (European Journal of Pediatric Surgery Reports, 2019)
The oncological safety of a laparoscopic approach for solid pseudopapillary tumors (SPTs) of the pancreas remains a matter of debate. We present the long-term follow-up of an adolescent girl with an SPT in the pancreatic tail. A multimodality workup including magnetic resonance imaging (MRI) revealed a complex, spherical mass of 4.4 cm × 3.6 cm × 4 cm most likely located in the pancreatic tail. All routine laboratory investigations and tumor markers were within normal limits (alpha fetoprotein [AFP], cancer antigen 125 [CA125], CA 19–9, carcinoembryonic antigen [CEA], adrenocorticotropic hormone [ACTH]). Diagnostic laparoscopy was performed to verify the origin of the tumor in the pancreatic tail. In a three-port technique the tumor was mobilized of the splenic vessels until a distal pancreatectomy could be completed. Histopathological examination confirmed the complete resection of a low-grade malignant SPT. The postoperative course was unremarkable. Regular pediatric oncological follow-up examinations for 3 years, including MRI every 6 months, ruled out recurrence and confirmed preservation of splenic and pancreatic functions. While data about the technical feasibility of a laparoscopic approach to pancreatic SPT are already available, this pediatric case report adds a long-term oncological and functional success to the available literature.
Keywords: Frantz tumor; solid pseudopapillary tumor; pancreas; oncology; laparoscopy